Etude phénotypique et Epidémiologique du cancer du sein - MEZIANI, HASNIA; MEFLAH, NORA (My University, 2023)
Breast cancer is a real public health problem, whether in Algeria or worldwide. In our country, it represents the first female cancer by order of frequency and the first cause of female mortality. We aim to study the epidemiological and anatomopathological parameters of breast cancer, compare our results with those of the literature and evaluate our immunohistochemical technique. This is a prospective study of 250 breast cases diagnosed in the Oncology department of the wilaya of Mostaganem, in 2023. The evaluation of the expression of the hormone receptors, the oncoproteinHER2 and the Ki67 antigen was carried out by the histological method and immunohistochemistry. The parameters studied in our retrospective study include age, tumor size, histological type, SBR grade, involvement of lymph nodes, hormone receptors. We looked at a total of 250 breast cancer cases. The age group most affected by this disease is that of [40-49], with extremes of 20 and 89 years and an average age of 50 years. Pathologically, the dominant histological type is infiltrating ductal carcinoma (88.4%) with a high SBR II histoprognostic grade (70.4%). The pT2 tumor size is the most frequent (44.8%). Lymph nodes are positive in 60.8% of cases. The hormone receptors are RE- are expressed in (22.4%) of cases, and RE+ (77.6%), RP- in (24.8%) of cases, and RP+ (75.2%), and l HER2 oncoprotein in (score 0: 43.2%, score 1: 24%, score 2: 8%, score 3: 24.8%) of cases. The ki67+++ antigen in (61.6%) of cases and Ki67- in (38.4%). Like most studies in the literature, we noted an association between ER and PR and between ER and HER2.
Keywords: breast cancer; invasive ductal carcinoma; invasive lobular carcinoma; immunohistochemistry